Radical Ideology Penetration Patterns Through Religious Study Activities - Abdurrahmansyah Abdurrahmansyah; Ade Akhmad Saputra; Nurseri Hasnah Nasution; Vicky Chandra; Juan Muliawan Fatrin (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
adicalism in the mosque environment is one of the social phenomena that needs serious attention. Mosques, as centres of worship and Islamic learning, can be effective means of spreading moderate ideology, but are also vulnerable to infiltration of radical ideology. This phenomenon occurs in various cities in Indonesia, including Palembang. This research aims to analyze the penetration patterns of the spread of radical ideology through recitation activities in Palembang City mosques. This research uses a qualitative approach with a case study method. The data source in this research, namely the primary source, is the chairman of the mosque takmir, chairman of the Idarah and Imarah section, as the administrator who has the authority to make decisions regarding mosque management such as the recitation schedule at the mosque. The secondary source of this research will be directed at the mosque congregation who are involved in every activity held at the mosque. Data collection in this research used interview, documentation and observation techniques. The stages of the data analysis process include data collection, data reduction, data presentation, and drawing conclusions and verification. The results of this research can be concluded as follows: The patterns of penetration of radical Islamic ideology from Salafi followers among residents and mosque congregations in Palembang include, among others, through the spread of Salafi ustadz as Friday preachers, through the distribution of books that have been explained. (syarah) from Salafi ulama circles, and through the distribution of message and video posts on Whatsapp Group.